Mafia Women: A Study on Language and Mental Representations of Women Engaged with Mafia Members - Schimmenti, Adriano; Giunta, Serena; Verso, Girolamo Lo (International Journal of Criminology and Sociology, 2014)
For a long time, women in the Mafia were considered victims who were unaware of the activities of the men in their families. However, it has recently been demonstrated that these women may play an important role in the organisation, particularly in the transmission of Mafia values. In this study, we explored the representations of self, relationships, and the Mafia world in women engaged with Mafia members. This was done by means of in-depth interviews and computer-assisted text analysis. A cluster analysis was applied to words used by the women in the interviews. Three clusters emerged that accounted for 85% of the principal contents of the interviews. These were interpreted as “representations of family”, “representations of social relationships”, and “ideals and values”. The analysis of words included in each cluster suggested that Mafia women are deeply involved in the transmission of traditional Sicilian values to their offspring. These ideals and beliefs are deeply rooted in the Mafia organisation and they involve attributing a central role to family, religion, and honor within the Mafia culture. Findings of the study could be positively used for developing appropriate preventative and social measures that may help these women change their ideals and beliefs related to the Mafia world, thus breaking the transmission of Mafia values.